Zero Student Lite: Model Inovasi dan Kreativitas Kepala Sekolah Di SMA Negeri 3 Jember - Indarsih, Fajar; Rahman, Fawait Syaiful (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
One of the efforts to improve Character Education is discipline. The discipline of entering the classroom, the discipline of carrying out the school discipline, and the discipline of improving learning achievement. One of the educational institutions in Jember district with low student discipline level is SMAN 3 Jember. The lack of discipline in school in SMAN 3 Jember school has been running for many years. The community knows the school with its low-level high discipline, lack of discipline in dealing with troubled students, and often empty hours. The focus of this article is on the innovation and creativity efforts of the principal of SMAN 3 Jember in suppressing the low rate of discipline of students. The method used is qualitative with the type of research library. The findings of this article are that SMAN 3 Jember school successfully innovates and creativity in improving the quality of educational institutions in student discipline. The success of SMAN 3 Jember reduces the low level of discipline of students entering the school through the Zero Student Lite Program. Zero Student Lite program is a program resulting from the innovation and creativity of the Principal to minimize the level of lack of discipline of students who have been rooted for years. Mechanism of implementation of Zero Student Lite Program: first, coordinating and cooperating with stake holders. Second, give punishment or coaching to students late to school by conducting observation (outdoor learning). Third, students are assigned to record and describe the findings of observations. Fourth, collect the results of observation records the next day as evidence ofattendance filling.